EFFECT OF INTRAVENOUS LIGNOCAINE ON HEMODYNAMIC VARIABLES DURING INTRAOPERATIVE AND POST-OPERATIVE PERIOD - KHANDEKAR, SHEETAL; TITLER, SANJIV; SHYAMBARAN; DR, RAKESH; SINGH, RAVINDRA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to assess the efficacy of intravenous lignocaine on hemodynamic variables during intraoperative and post-operative periods and in relieving post-operative pain in major abdominal surgery. Methods: To investigate the effects of lidocaine, we designed a double-blind study. We enrolled 100 patients of ASA Grade I or II slated for major abdominal procedures. Each participant received either lidocaine or a saline placebo intravenously. After surgery, we monitored their pain levels, vital signs, and any potential side effects. Results: Our study revealed clear differences in heart rate, blood pressure (both systolic and diastolic), and overall arterial pressure between the lidocaine and placebo groups. Notably, the lidocaine group experienced fewer side effects, such as nausea, vomiting, headache, and shivering, compared to the control group. Conclusion: Intravenous lidocaine reduces intraoperative and post-operative pulse rate and blood pressure in major abdominal surgery. It delays analgesic needs and lowers the incidence of nausea, vomiting, chills, and headache compared to controls.